2013
DOI: 10.1093/ntr/ntt067
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Disposition of Nicotine and Metabolites in Rat Brain and Plasma

Abstract: Nicotine and metabolite distribution differs between adolescent and adult rats. These data suggest that adolescent rats metabolize nicotine to some metabolites faster than adult rats. Further studies are needed to investigate the potential correlation between age, drug distribution, and nicotine addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…The lower serum and brain nicotine levels in adolescents versus adults following injection of 0.5 mg/kg nicotine in Experiment 2 is consistent with recent findings ( Vieira-Brock et al, 2013 ; Craig et al, 2014 ). We also found higher brain:serum nicotine concentration ratios in adolescents compared to adults, suggesting greater penetration of nicotine into brain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lower serum and brain nicotine levels in adolescents versus adults following injection of 0.5 mg/kg nicotine in Experiment 2 is consistent with recent findings ( Vieira-Brock et al, 2013 ; Craig et al, 2014 ). We also found higher brain:serum nicotine concentration ratios in adolescents compared to adults, suggesting greater penetration of nicotine into brain.…”
Section: Discussionsupporting
confidence: 91%
“…A secondary goal was to examine age differences in these effects. Therefore, following establishment of nicotine dosing conditions that accounted for age differences in nicotine pharmacokinetics (see Vieira-Brock et al, 2013 ; Craig et al, 2014 ) and produced similar nicotine serum levels across ages (Experiment 2), we evaluated effects of mecamylamine alone and mecamylamine combined with acute nicotine on somatic signs in both adolescents and adults (Experiment 3).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental differences in nicotine metabolism could be a source of difference in the threshold dose of nicotine that supports initiation of self-administration behavior seen here. Vieira-Brock et al 32 and Craig et al 33 found that following a subcutaneous injection of nicotine, blood and brain nicotine levels were lower in adolescent male rats compared to adult male rats. Similarly, following an intravenous injection Craig et al 33 observed that although the initial peak in blood nicotine levels did not differ between adolescents and adults, the levels declined more rapidly in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…For plasma quantification, 100 μl plasma samples were prepared as previously described (Craig et al , 2014; Vieira-Brock et al , 2013). The prepared dialysate and plasma samples were then analyzed by LC-MS as previously described (Craig et al , 2014).…”
Section: Methodsmentioning
confidence: 99%